Orthophotography and its Applications in the Recording of Buildings - Seeni Mohd., Mohd. Ibrahim (Penerbit UTM Press, 1984)
This paper deals with the orthophoto technique of recording buildings. Firstly, it focuses on the concept of orthophotography where the principles of differential rectification are described. Secondly, the errors inherent in the orthophotographic process which would affect the accuracy and pictorial Quality of the final product, that is, the orthophoto itself are discussed. Among the errors, system errors followed by scanning errors have the major effect on the accuracy and pictorial quality. Finally, the writer presents his observations from the studies carried out on four different types of building surfaces.